Teachers as Health Workers in the Philippines - Lasco, Gideon (Archīum Ateneo, 2024)
Objectives While the chronically overburdened state of public school teachers in the Philippines is well-established, little is known about how they specifically provide ‘care’ and attend to their students’ health in the workplace. This article addresses that knowledge gap by illustrating the many forms of ‘health work’ undertaken by public school teachers on a daily basis, and analyzing the concrete challenges they face in doing such work. In so doing, this article provides a qualitative construction of school teachers as ‘health workers’ in the country. Methods This article draws from two focus group discussions conducted in Southern Luzon and Eastern Visayas between November 2018 to May 2019, as part of a multi-sited study on the health-related challenges faced by low- and middle-income Filipinos. A total of 19 teachers participated in those two discussions. We used the principles of thematic analysis to code and analyze the discussion transcripts. Results Teachers regularly fulfill various tasks that can be considered health work, including measuring students’ anthropometrics; supervising and administering government programs like deworming, feeding programs, and vaccinations; providing first-aid and various forms of immediate medical attention; addressing students’ mental and psychological health concerns; and working with students’ families in ways that resemble social work. However, the study participants largely considered themselves unqualified to do health work, often sacrificed their own personal health and interpersonal relationships to take on the additional burden of health work, and felt they received insufficient institutional support. Conclusion Doing health work not only takes away from actual teaching time, but also comes at the expense of teachers’ own health. Hiring the appropriate personnel to conduct health work and improving legal safeguards are possible solutions to ameliorating the present working conditions of teachers. Yet, the larger and more long-term conversation demands the prioritiziation of teachers’ well-being and overall quality of life, and recognizing the cruciality of a healthy work-life balance for them. Future studies should involve more diverse geographic sites and teacher populations, and utilize more focused forms of analysis (e.g., comparative, policy-driven).